A invenção de Hugo Cabret - Selznick, Brian 1966- (Ed. SM, 2007)
When twelve-year-old Hugo, an orphan living and repairing clocks within the walls of a Paris train station in 1931, meets a mysterious toyseller and his goddaughter, his undercover life and his biggest secret are jeopardized